Mass Media in The Socialization of E-Government Policiesabout Online Electronic Applications Services (E- Open) - Rohmawati, T; Solihin, O; Mogot, Y; Aulia, K P (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The purpose of this study was written to find out about the mass media of e-government policy socialization through online service electronic applications (E-OPEN) at the Bekasi City population and civil registration service. The focus in this research is on the mass media socialization of e-government policies through electronic online service applications (E-OPEN) at the Bekasi City population and civil registration service. This paper is the result of research using a descriptive qualitative approach. Data collection techniques that researchers use are literature studies and field studies which are divided into three, namely observation, interviews and documentation. The technique for determining informants in this study used a purposive technique, starting from the head of the Bekasi City Disdukcapil planning department, the apparatus and admins who manage the Bekasi City Disdukcapil E-OPEN application to the public using the E-OPEN application to obtain information about mass media policy outreach to the application. E-OPEN. The results of this study indicate that the mass media used in disseminating E-Government policies through Electronic Online Services (E-OPEN) applications include Instagram @disdukcapilkotabekasi, Twitter @Disdukcapil2, Youtube Disdukcapil Kota Bekasi, Website https://disdukcapil.bekasikota. go.id. The existence of this mass media provides benefits for the people of Bekasi regarding the policies issued by the Bekasi City Government.